Reasons for unsafe abortion in Iran after pronatalist policy changes: a qualitative study - Arezoo Haseli; Nasrin Rahnejat; Dara Rasoal (Reproductive Health, 2024)
Abstract Background In Iran, restrictive abortion laws have led to widespread unsafe abortions, posing significant health risks. The 2021 Family and Youth Protection Law further restricted access to reproductive health services in an effort to boost birth rates. The purpose of this qualitative study is to explore the reasons women sought abortions in an illegal context, based on their own experiences. Methods This exploratory qualitative study involved in-depth interviews with 46 women in Kermanshah, Iran, between April and August 2024. All participants had experienced incomplete abortions after undergoing unsafe procedures. Data were analyzed using conventional content analysis and thematic analysis with MAXQDA 10 software to identify key themes in the women's experiences. To ensure the study's rigor, we applied Guba and Lincoln’s criteria, including credibility, dependability, confirmability, and transferability. Results Five main themes emerged from the interviews: economic hardship, pursuit of a prosperous life, unstable marital relationships, health and fertility issues, and cultural factors. Economic challenges, such as unemployment and lack of basic necessities, were the most frequently cited reasons for seeking unsafe abortions. Health issues, including unplanned pregnancies and fear of fetal anomalies, also played a significant role, alongside cultural stigmas related to age, illegitimacy, and gender preferences. Conclusion This study sheds light on the multifaceted factors driving unsafe abortions in Iran following pronatalist policy changes. A holistic approach is recommended to address the interconnected economic, social, and cultural challenges that contribute to this issue. By implementing such comprehensive strategies, policymakers and stakeholders can work to reduce the prevalence of unsafe abortion practices and foster improved health and well-being for women.